A review on auditory space adaptations to altered head-related cues - Mendonça, Catarina (Frontiers in Neuroscience, 2014)
In this article we present a review of current literature on adaptations to altered head-related auditory localization cues. Localization cues can be altered through ear blocks, ear molds, electronic hearing devices, and altered head-related transfer functions (HRTFs). Three main methods have been used to induce auditory space adaptation: sound exposure, training with feedback, and explicit training. Adaptations induced by training, rather than exposure, are consistently faster. Studies on localization with altered head-related cues have reported poor initial localization, but improved accuracy and discriminability with training. Also, studies that displaced the auditory space by altering cue values reported adaptations in perceived source position to compensate for such displacements. Auditory space adaptations can last for a few months even without further contact with the learned cues. In most studies, localization with the subject's own unaltered cues remained intact despite the adaptation to a second set of cues. Generalization is observed from trained to untrained sound source positions, but there is mixed evidence regarding cross-frequency generalization. Multiple brain areas might be involved in auditory space adaptation processes, but the auditory cortex (AC) may play a critical role. Auditory space plasticity may involve context-dependent cue reweighting.